2019
DOI: 10.1096/fj.201802121rr
|View full text |Cite|
|
Sign up to set email alerts
|

Osteopontin plays important roles in pulmonary arterial hypertension induced by systemic‐to‐pulmonary shunt

Abstract: Recent studies indicated that osteopontin (OPN) was involved in the genesis and progression of pulmonary arterial hypertension (PAH); however, its role in congenital heart disease–associated PAH (CHD/PAH) remains unknown. Our results showed that OPN was increased in lungs and plasma of patients with Eisenmenger syndrome; moreover, OPN and αvβ3‐integrin expression levels were augmented in rat lungs exposed to systemic‐to‐pulmonary shunt. Cell culture assay demonstrated that distal pulmonary arterial smooth musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…From N-terminus to Cterminus, these include the arginine-glycine-aspartic acid (RGD) cell-binding sequence, a serinevaline-valine-tyrosine-glycine-leucine-arginine (SVVYGLR) domain, mediating the interaction between OPN and integrin receptors α4β1 and α9β1, a calcium-binding site and a heparin-binding site. Our LC-MS analysis of OPN digests by ADAMTS8 identified cleavage sites at Tyr 33 -Asn 34 , Asn 53 -Leu 54 , Asp 217 -Asp 218 , Ser 225 -His 226 , His 226 -Lys 227 , Gln 228 -Ser 229 , Ser 229 -Arg 230 , Glu 251 -Leu 252 , Glu 263 -Phe 264 , and Phe 264 -His 265 . Three of these, Asn 53 -Leu 54 , Asp 217 -Asp 218 and Gln 228 -Ser 229 , were significant already after 2 h digestion.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…From N-terminus to Cterminus, these include the arginine-glycine-aspartic acid (RGD) cell-binding sequence, a serinevaline-valine-tyrosine-glycine-leucine-arginine (SVVYGLR) domain, mediating the interaction between OPN and integrin receptors α4β1 and α9β1, a calcium-binding site and a heparin-binding site. Our LC-MS analysis of OPN digests by ADAMTS8 identified cleavage sites at Tyr 33 -Asn 34 , Asn 53 -Leu 54 , Asp 217 -Asp 218 , Ser 225 -His 226 , His 226 -Lys 227 , Gln 228 -Ser 229 , Ser 229 -Arg 230 , Glu 251 -Leu 252 , Glu 263 -Phe 264 , and Phe 264 -His 265 . Three of these, Asn 53 -Leu 54 , Asp 217 -Asp 218 and Gln 228 -Ser 229 , were significant already after 2 h digestion.…”
Section: Discussionmentioning
confidence: 89%
“…The gene found to be most consistently upregulated was Spp1 , coding for secreted phosphoprotein 1 or osteopontin (OPN) ( Table S2 ). OPN stimulates growth and migration of PAH SMCs ( 33 , 34 ) and contributes to the highly proliferative, migratory and proinvasive phenotype exhibited by adventitial fibroblasts in PAH ( 35 ). OPN plasma levels increase in patients with PAH ( 33 , 35 , 36 , 37 ) and correlate with disease severity ( 37 ) and mortality ( 36 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The comprehensive analysis showed that the high expression of SPP1 should be a driver of PAH. It has been reported that SPP1 plays a role in PAH via enhancing pulmonary vascular smooth muscle cell (PVSMC) proliferation [50,51]. The expression level of SPP1 was related to the severity of PAH [52,53].…”
Section: Discussionmentioning
confidence: 99%